AL ISMU GHOIRI AL-MUNSHARIFI FI KITAB MUKHTASHAR IBNU ABI JAMRAH LI ASY SYANWANI - Ibtisam, Ibtisam; Umar, Nur Hasaniyah (Annual International Conferences on Language, Literature, and Media, 2021)
This research aims to identify the types and characteristics of the indefinite noun in the book Mukhtasar Ibn Abi Jamra by Al-Bukhari, written by Muhammad bin Ali Al-Shafi’i Al-Shanawani. The qualitative descriptive approach is used. The main data source is "The Mukhtasar Book of Ibn Abi Jamra by Al-Bukhari". The secondary data sources are the book and other periodicals related to the research topic. Miles and Huberman's theory was used to analyze the data involving data reduction, presentation, and summary. The result shows nine types of indefinite nouns, with 316 nouns. As for its characteristics in the existing vowel standing in the presence of two vowels, for feminine with the shortened thousand is represented by the names of people, and for feminization with the extended thousand, in which the names of the chain of narrators are represented.